Strategi E Commerce dalam Memilih Hukum dan Forum untuk Menghindari Konflik Yurisdiksi pada Transaksi Lintas Batas - Allaysha Adindaputri Kirani; Gunardi Lie (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze e-commerce strategies in selecting applicable law and jurisdiction to avoid conflicts of jurisdiction in cross-border transactions. This study employs a normative legal method using legislative, conceptual, and comparative approaches to analyze the selection of applicable law and jurisdiction in cross-border e-commerce transactions. The data used consists of primary and secondary legal materials collected through a literature review. The analysis was conducted qualitatively using descriptive-analytical and legal interpretation methods, as well as deductive reasoning to formulate strategies for minimizing jurisdictional conflicts. The research findings indicate that the application of the principle of freedom of contract, combined with international instruments and digital technology, can serve as an effective strategy for e-commerce actors to minimize jurisdictional conflicts and litigation risks. This strategy not only provides legal protection, particularly for SMEs, but also enhances the trust of global partners and competitiveness in the international market through the use of clear contract clauses, hybrid forums, and technological support such as blockchain and ODR.